Keith Haring, 1958-1990 : a life for art - Kolossa, Alexandra; Haring, Keith (Hong Kong : Taschen, 2007)
Profiles the life and work of twentieth-century artist Keith Haring, with color reproductions of his work and an overview of the people, places, and events that shaped his methods.
Cover title: Haring.
Translated from the German.
Includes bibliographical references (p. 96).
Adult
Keywords: Haring, Keith -- Criticism and interpretation; Haring, Keith; Art, Modern -- 20th century; Artists -- United States -- Biography; Pop art -- United States; Art -- 20th century; Artists -- United States -- Biography; Modernism in art; Pop art